Application of Multiplanar Volume Reconstruction Technique for the Assessment of Electrode Location and Analysis of the Correlation to Cochlear Programming and Performance in Common Cavity Deformity - Wei, Xingmei; Zhang, Huaiyu; Lu, Simeng; Yang, Mengge; Chen, Biao; Chen, Jingyuan; Zhang, Lifang; Liu, Sha; Xian, Junfang; Li, Yongxin; Kong, Ying (Frontiers in Neurology, 2022)
Purpose: Owing to the characteristic anatomy, cochlear implantation (CI) for common cavity deformity (CCD) has resulted in varied outcomes and frequent facial and vestibular nerve stimulation. The current study analyzed the correlation among the distance between each electrode and cavity wall (abbreviation, D), programming parameters, and performances outcomes. Materials and Methods: The current, retrospective study included 25 patients (27 ears) with CCD underwent CI. The multiplanar volume reconstruction (MPVR) techniques were employed to reconstruct and evaluate the postoperative temporal bone CT. The D and maximum comfortable level (MCL) six months after CI, facial and vestibular nerve stimulation, and outcomes one, two, and three years after CI pertaining to the questionnaires were documented and analyzed. Results: The patients were divided into symptomatic (10, 37%) and asymptomatic (17, 63%) groups according to with or without facial and vestibular nerve stimulation. The MCL pertaining to the symptomatic group was significantly lower than asymptomatic group, but Categories of Auditory Performance (CAP) scores one year after surgery was better (p<0.05). The subjects were divided into flat (12, 44.4%) and curved (15, 55.6%) groups based on the contour of MCL map. The MCL and D were lower and shorter in the curved group than the flat group, and CAP score one year after surgery and Speech Intelligibility Rating (SIR) three years after surgery were better (p<0.05). Conclusion: Although abnormal reactions such as facial and vestibular nerve stimulation were observed to be more frequent, lower MCL and better outcomes were observed in relation to the shorter D.